Subordination in Italian and English: Implications for Second Language Acquisition - Patrizia Giuliano; Simona Anastasio (Discours)
Our study focuses on morpho-syntactic complexity, trying to identify the specific subordinated modalities of organizing and packaging information in a narration. This purpose will be achieved by combining the morpho-syntactic analysis with the type of contents that subordinate clauses convey with respect to the informational flux of textual structure (foreground vs. background alternation). A functionalist and enunciative framework is adopted. The following questions will be addressed: (1) which types of morpho-syntactic structures – main or subordinated, finite or non finite – are exploited to convey the subordinated contents selected? (2) do the informants tend to hierarchize the expressed contents? (3) which types of semantic and/or logical components (temporality, causality, etc.) are selected to be narrated and highlighted through subordination? We shall demonstrate that only the interaction of several factors – core morphological facts, interactional and discourse habits – can exhaustively explain the textual perspectives observed in our L1 and L2 data, with interesting consequences for second language acquisition.